PENERAPAN PRINSIP-PRINSIP GOOD GOVERNANCE DALAM PELAYANAN PUBLIK DI KECAMATAN CIGUGUR KABUPATEN KUNINGAN - -, Ediyanto (Decision, 2020)
This research focuses on the study of the Application of the Principles of Good Governance in Public Services in Cigugur District, Kuningan Regency. Cigugur Subdistrict Kuningan Regency has so far applied the principles of good governance, especially in the implementation of public services. but in its implementation is still not optimal. With the lack of adequate infrastructure in the Cigugur Subdistrict office, the employees provide less than optimal services to the community, especially in population administration services and services related to community activities programs in the Cigugur sub-district. Phenomenon in the field The application of the principles of good governance in public services in Cigugur Subdistrict, Kuningan Regency so far has not run optimally in accordance with interviews from the sub-district and cigugur Kuningan community. Judging from the still not optimal Accountability and Transparency in the implementation of public services in Cigugur Subdistrict, Kuningan Regency, for example, long-winded service procedures, uncertainty of time and prices that make services difficult to reach naturally by the public. This causes mistrust to the service providers so that people look for alternative ways to get services through certain methods, namely by providing additional costs. In providing public services. The method used in this research is qualitative method. Data collection techniques through literature study, observation and interviews. Seeing from this problem, the researcher gave a suggestion, namely that the Accountability of public services in the District of Cigugur, Kuningan Regency needs to be improved by making better operational service standards so that the timeliness in service can be completed in accordance with the specified time. The need for transparency with regard to the costs of obtaining documents in full to the end so that the public knows their obligations in managing land documents. Keywords: good governance, public service